Scientific charge-coupled devices - Janesick, James R. (SPIE monograph, 2001)
The invention of the charge-coupled device 30 years ago was the beginning of a remarkable image capture technology that has changed the course of imaging in fields ranging from astronomy to biotechnology. This book presents a comprehensive history, tutorial, and state-of-the-art description of CCDs and is intended for scientists, engineers, imaging hardware managers, and graduate students.